Surface Acoustic Wave (SAW) Tags Structures and Models - Lisovskij, A.; Rupkus, S.; Janeliauskas, A. (Elektronika ir Elektrotechnika, 2005)
Surface acoustic wave (SAW) tags have a perspective future. For better read range and technology improvement is reasonable to use single destination converters, working on the main frequency harmonics. In the paper provided single destination double section SAW tag model, which assessed charge distribution in electrodes type, secondary effects, loss and waves speed change constituents. There is provided unique SAW tag reflection element and single destination converter technological decision, which allows to increase energy localization and reflection coefficient. The expressed conclusions are presented. Ill. 5, bibl. 5 (in Lithuanian; summaries in Lithuanian, English and Russian).